THE IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL IN DEVELOPING STUDENTS’ HIGHER ORDER THINKING IN SOCIAL STUDIES LEARNING (A Descriptive Study on Teacher in SMP Negeri 40 Bandung) - Chadziqoh, Niswatul (Universitas Pendidikan Indonesia, 2017)
Abstract-This research is motivated by the results of initial observation on social studies learning activities conducted by one of the teachers at SMP Negeri 40 Bandung indicating that the implementation of Problem Based Learning (PBL) model is able to develop students' higher order thinking in social studies learning. PBL learning model needs to be developed by the teacher during the learning activities so that students have higher order thinking ability to provision them in facing various challenges in the 21st century era. For that matter, this study aims to describe the implementation of learning PBL model to develop students’ higher order thinking ability. The method used in this study is descriptive method with the subject of research is social studies teacher and students of class IX-D SMP Negeri 40 Bandung, consisting of 30 students. Data collection techniques used to obtain the data on the implementation of PBL model to develop students' higher order thinking ability is observation. The results showed that the implementation of the PBL model can develop students' higher order thinking skills. This is supported by observational data on students' higher order thinking activities developed through the PBL model at the first and second meetings that showed improvement in each of the higher order thinking level areas i.e. analysis, evaluation, and creation.Keywords: Problem Based Learning (PBL) Model, Higher Order Thinking